Performance analysis of finned photovoltaic/thermal solar air dryer with using a compound parabolic concentrator. (15th December 2021) - Shoeibi, Shahin; Kargarsharifabad, Hadi; Mirjalily, Seyed Ali Agha; Zargarazad, Mojtaba
Highlights: The solar air dryer with using finned photovoltaic panel was investigated. The hybrid system greatly increase the electrical and thermal efficiencies. The highest cost per power is achieved in photovoltaic/thermal solar air dryer with 24 fins. The highest CO2 mitigation of the system during lifetime was equal to 44.19 tons. Abstract: The photovoltaic thermal system is widely used in producing electricity and thermal from solar energy. This study focused on improving the performance of the solar air heater coupled with a finned photovoltaic system as an absorber plate. The compound parabolic concentrator was installed on the right and left sides of the solar panel to enhance the absorptivity of solar radiation. The V-shape fins were placed under the solar panel to reduce the temperature of the photovoltaic system. Ambient air entered the solar dryer by a fan, passed through the solar panel, flowed on the fins installed under the panel, and exited the solar dryer. Four experiments were performed using 0, 8, 16, and 24 fins. The ambient air temperature increased by the convective heat transfer through the panel and fin, and the surface temperature of the panel decreased. The hot outlet air was used as an air dryer. The thermal and electrical efficiencies, economic, and enviroeconomic of the Photovoltaic/thermal solar air dryer were investigated. The results showed that the CO2 mitigation of the system using 24, 16, and 8 fins improved by 35.1%, 22.8%, and 10.7%, respectively. Also, the electrical and thermal efficiencies of the photovoltaic/thermal solar air dryer using 24 fins were enhanced by 28.7% and 30.6%, compared to those without fins. Moreover, the power generation cost of the system using 24, 16, 8, and 0 fins was equal to 0.206, 0.196, 0.190, and 0.186 $/kWh, respectively.